Upper Limbs Kinematics of Liberation Moment in the Elite Archers - Mohsen Damavandi; Nafiseh Bakhshandeh-zahmati; Mehrdad Fathi (Biyumikānīk-i varzishī)
Objective: The purpose of this study was to evaluate the kinematics of liberation moment in the elite archers. Methods: Ten elite archers (male = 5, female = 5), who were the members of the provincial and national teams, were studied. The trunk and upper extremities of the subjects were determined by 5 reflective markers. Each archer performed 10 successful trials. Using Motion Analysis System (150 Hz with a low pass filter having a cut-off frequency of 7 Hz) and based on markers’ coordination, the angles and angular velocities of the shoulder, elbow, and wrist of pulling hand in the sagittal plane at the moment of liberation were calculated. Results: Means (SD) of the shoulder, elbow, and wrist angles were 93.1 (4.0), 135.7 (5.7), 15.3 (2.8) °, respectively. Means (SD) of the shoulder, elbow, and wrist angular velocities were 55.4 (23.5), 38.4 (16.1), 81.9 (36.6) °/s, respectively. Conclusion: The fast wrist extension causes a quick arrow release and enhancements in the results of archery. In addition, coordination between elbow flexion and shoulder extension assists the archer to pull the bow at its maximum range. These amounts and kinematic relations can serve as a criterion for coaches and elementary archers to enhance their level of performance.